Preparation and evaluation of injectable microsphere formulation for longer sustained release of donepezil - Ji, Yun Bae; Lee, Soyeon; Ju, Hyeon Jin; Kim, Hee Eun; Noh, Jung Hyun; Choi, Sangdun; Park, Kinam; Lee, Hai Bang; Kim, Moon Suk (Journal of Controlled Release, 2023)
In this study, donepezil-loaded PLGA and PLA microspheres (Dp-PLGA-M/Dp-PLA-M) and Dp-PLA-M wrapped in a polyethylene glycol-b-polycaprolactone (PC) hydrogel (Dp-PLA-M/PC) were prepared to reduce the dosing frequency of injections to treat Alzheimer's disease patients. Dp-PLGA-M and Dp-PLA-M with a uniform particle size distribution were repeatably fabricated in nearly quantitative yield and with high encapsulated Dp yields using an ultrasonic atomizer. The injectability and in vitro and in vivo Dp release, biodegradation, and inflammatory response elicited by the Dp-PLGA-M, Dp-PLA-M, and Dp-PLA-M/PC formulations were then compared. All injectable formulations showed good injectability with ease of injection, even flow, and no clogging using a syringe needle under 21-G. The injections required a force of <1 N. According to the biodegradation rate of micro-CT, GPC and NMR analyses, the biodegradation of Dp-PLA-M was slower than that of Dp-PLGA-M, and the biodegradation rate of Dp-PLA-M/PC was also slower. In the Dp release experiment, Dp-PLA-M sustained Dp for longer compared with Dp-PLGA-M. Dp-PLA-M/PC exhibited a longer sustained release pattern of two months. In vivo bioavailability of Dp-PLA-M/PC was almost 1.4 times higher than that of Dp-PLA-M and 1.9 times higher than that of Dp-PLGA-M. The variations in the Dp release patterns of Dp-PLGA-M and Dp-PLA-M were explained by differences in the degradation rates of PLGA and PLA. The sustained release of Dp by Dp-PLA-M/PC was attributed to the fact that the PC hydrogel served as a wrapping matrix for Dp-PLA-M, which could slow down the biodegradation of PLA-M, thus delaying the release of Dp from Dp-PLA-M. Dp-PLGA-M induced a higher inflammatory response compared to Dp-PLA-M/PC, suggesting that the rapid degradation of PLGA triggered a strong inflammatory response. In conclusion, Dp-PLA-M/PC is a promising injectable Dp formulation that could be used to reduce the dosing frequency of Dp injections.
Keywords: Biodegradation rate; Donepezil; Dosing frequency; Inflammatory response; Injectability; Injectables; Long lasting; Long-lasting release; Release pattern; Sustained release; Biocompatible Materials; Delayed-Action Preparations; Donepezil; Humans; Hydrogels; Lactic Acid; Microspheres; Particle Size; Polyesters; Polyglycolic Acid; Polylactic Acid-Polyglycolic Acid Copolymer; Biodegradation; Donepezil; Inflammatory response; Injectability; Long-lasting release; Microsphere